Olfactory Function, Genetic Predisposition, and Cognitive Performance in Chinese Adults - Yang, Xianyi; Si, Jing; Lin, Shuchun; Zhou, Xiaofeng; Zhang, Hui; Sun, Zhonghan; Pu, Yanni; Li, Qian; Qiu, Jiange; Wang, Lin; Song, Chunhua; Yuan, Changzheng; et al. (Current Alzheimer Research, 2021)
Objective: The objective of this study is to examine the association of olfactory function and genetic predisposition of Alzheimer’s disease (AD) with cognitive performance in adults. Methods: A total of 2049 Chinese adults from Rugao Longevity and Ageing Study (RuLAS, n=1460, mean age 78 years) and Central China Cohort (CCC, n=589, mean age 48 years) were included in this study. A standard interview-based survey, clinical information, and blood samples were collected in both cohorts. Olfactory function in terms of olfactory identification was measured by the brief version of the Chinese Smell Identification Test consisted of 18 full points. Cognitive performance was measured by the Chinese version of the Mini-mental State Examination. A genetic risk score (GRS) was calculated from 5 single nucleotide polymorphisms, which were robustly related to Alzheimer’s disease in Caucasians and cognitive performance in our Chinese population. Results: In the pooled analyses, participants at the lowest quartile of olfactory function had significantly higher odds of cognitive impairment (adjusted odds ratio [95% CI] =1.45 [1.00 to 2.09], Ptrend =0.005), and such association was stronger among participants with a stronger genetic predisposition of Alzheimer’s disease (β coefficient±SE, -0.06±0.03 in participants with a lower GRS vs. -0.19±0.05 in those with a higher GRS, respectively, Pinteraction=0.01). Similar associations were observed in RuLAS (P-trend=0.06) and in CCC (P-trend<0.001). Conclusion: In this study, a decreased olfactory function was associated with worse cognitive performance in adults, especially among participants with a higher genetic risk of Alzheimer’s disease. Further studies are warranted to evaluate the causal relationship between olfaction and cognitive performance.
Keywords: population study